(untitled) (Vietnam Journal of Community Medicine, 2026)
ABSTRACT Objective: This study aimed to determine the prevalence of goiter among children aged 8–10 years in Quang Ninh Province in 2021. Subject and method: This is a cross-sectional descriptive study was conducted among 1.800 children aged 8–10 years across 13 districts, towns, and cities in the province. Data were collected through clinical examination, thyroid ultrasound, urine sampling, and urinary iodine level testing. Results: The results showed that the prevalence of goiter among children in Quang Ninh was 4,11%, with most cases classified as grade 1a (1,72%) and grade 1b (2,39%). Nodular goiter accounted for a higher proportion (58.11%) than diffuse goiter (41,89%). The median urinary iodine concentration was 11,06 µg/dL, and 90,11% of children had urinary iodine levels ≥10 µg/dL. Conclusion: The prevalence of goiter met the World Health Organization (WHO) recommended threshold of ≤5.0%, indicating a level eligible for the declaration of elimination as a public health problem. However, population-level urinary iodine assessment suggested that a considerable number of children still require daily iodine supplementation to prevent goiter and other iodine deficiency disorders.